An Exponent of Scottish Common Sense Philosophy in Revolutionary South America: José Joaquín de Mora. Issue 2 (November 2018) - Macintyre, Iona
Abstract : Revolutionary movements in nineteenth-century South America saw the region's historic grounding in scholasticism confronted by the ideas of the eighteenth-century French Enlightenment. This article examines a subsequent development: Spanish liberal man of letters José Joaquín de Mora's attempt to implant Scottish common sense philosophy as the dominant school in the republics that were emerging from Spanish rule and gradually forming nationally as Argentina, Bolivia, Chile and Peru. Furthering our knowledge of Scottish intellectual influence abroad, Mora's enterprise also illuminates two contentious issues of the period in Spanish America, namely how to cultivate young minds in a revolutionary context, and the place of European culture, in this case Scottish, in the immediate post-colonial period.